Determination and risk assessment of naturally occurring genotoxic and carcinogenic alkenylbenzenes in nutmeg‐based plant food supplements. Issue 10 (29th May 2017) - Al‐Malahmeh, Amer J.; Alajlouni, Abdalmajeed M.; Ning, Jia; Wesseling, Sebastiaan; Vervoort, Jacques; Rietjens, Ivonne M. C. M.
Abstract: A risk assessment of nutmeg‐based plant food supplements (PFS) containing different alkenylbenzenes was performed based on the alkenylbenzene levels quantified in a series of PFS collected via the online market. The estimated daily intake (EDI) of the alkenylbenzenes amounted to 0.3 to 312 μg kg −1 body weight (bw) for individual alkenylbenzenes, to 1.5 to 631 μg kg −1 bw when adding up the alkenylbenzene levels assuming equal potency, and to 0.4 to 295 μg kg −1 bw when expressed in safrole equivalents using toxic equivalency factors (TEFs). The margin of exposure approach (MOE) was used to evaluate the potential risks. Independent of the method used for the intake estimate, the MOE values obtained were generally lower than 10000 indicating a priority for risk management. When taking into account that PFS may be used for shorter periods of time and using Haber's rule to correct for shorter than lifetime exposure it was shown that limiting exposure to only 1 or 2 weeks would result in MOE values that would be, with the presently determined levels of alkenylbenzenes and proposed uses of the PFS, of low priority for risk management (MOE > 10000). It is concluded that the results of the present paper reveal that nutmeg‐based PFS consumption following recommendations for daily intake especially for longer periods of time raise a concern. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : A margin of exposure (MOE) based risk assessment of nutmeg‐based PFS containing different alkenylbenzenes was performed based on alkenylbenzene levels detected in these samples. Estimated daily intake (EDI) values obtained adding up the alkenylbenzene levels assuming equal potency, or expressing them in safrole equivalents using toxic equivalency factors (TEFs), resulted in MOE values lower than 10000 upon long‐term intake but higher than 10000 considering short‐term exposure. It is concluded that nutmeg‐based PFS consumption does not always present a priority for risk management.